Analisis Kesesuaian Karir Berdasarkan Potensi Dan Minat Santri Tahfidz Di Pondok Pesantren Satu Qur’an - Fadhilah, Sinta Rahmatil; Maharani, Hikma Dwi Putri; Marlina, Marlina; Ambarwati, Jian; Tuzzaria, Atia; Gunawan, Teddy (JIGC (Journal of Islamic Guidance and Counseling), 2024)
Islamic boarding schools, as Indonesia's oldest Islamic educational institutions, play a crucial role in shaping the character and morals of future generations. Pesantren Satu Qur'an Jambi, established in 2015, aims to produce future leaders with noble character and independence. However, one challenge in tahfidz education is the lack of focus on developing skills relevant to the workforce. This study evaluates the impact of pesantren tahfidz education on students' employability skills and assesses how the curriculum supports their career preparation in both religious and non-religious fields. Using a qualitative approach, the research examines the effect of pesantren education on students' work skills and career choice alignment with their potential and interests. The findings indicate that students often face conflicts between spiritual goals and worldly needs, requiring career counseling guidance to better plan their future.